OBJECTIVE MAINTAINABILITY MEASUREMENT MODEL FOR OBJECTORIENTED SOFTWARE DESIGN - BAJEH, AMOS ORENYI (2014)
Software maintainability is an important quality attribute due to the fact that the maintenance phase of the Software Life Cycle has been attributed to be the most costly phase in terms of software budget and programmers' effort. Software metrics, which is the measurement of software structural and quality attributes, can be used to facilitate the engineering of quality into software, especially during the design phase of software development at which design refinement is easier and less costly than after implementation or when the software is already in use.